2018
DOI: 10.5935/abc.20180098
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Epidemiology in Portuguese-Speaking Countries: data from the Global Burden of Disease, 1990 to 2016

Abstract: BackgroundPortuguese-speaking countries (PSC) share the influence of the Portuguese culture but have socioeconomic development patterns that differ from that of Portugal.ObjectiveTo describe trends in cardiovascular disease (CVD) morbidity and mortality in the PSC between 1990 and 2016, stratified by sex, and their association with the respective sociodemographic indexes (SDI).MethodsThis study used the Global Burden of Disease (GBD) 2016 data and methodology. Data collection followed international standards f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
42

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 25 publications
0
42
0
42
Order By: Relevance
“…Dentre estes países, em 2015, os Índices Sócio Demográficos (IDS) mais baixos eram 0,28 e 0,29 na Guiné-Bissau e Moçambique, respectivamente, enquanto que no Brasil (0,66), o IDS se aproximava do de Portugal (0,75). Embora a mortalidade tenha diminuído ou permanecido estável em países com melhor IDS, o mesmo padrão não foi observado nos países com pior IDS, indicando o importante impacto da DCV e sua associação com fatores socioeconômicos (NASCIMENTO et al, 2012).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Dentre estes países, em 2015, os Índices Sócio Demográficos (IDS) mais baixos eram 0,28 e 0,29 na Guiné-Bissau e Moçambique, respectivamente, enquanto que no Brasil (0,66), o IDS se aproximava do de Portugal (0,75). Embora a mortalidade tenha diminuído ou permanecido estável em países com melhor IDS, o mesmo padrão não foi observado nos países com pior IDS, indicando o importante impacto da DCV e sua associação com fatores socioeconômicos (NASCIMENTO et al, 2012).…”
Section: Discussionunclassified
“…No Brasil, a hipertensão arterial sistêmica (HAS) atinge 32,5% (36 milhões) de indivíduos adultos, mais de 60% dos idosos, contribuindo direta ou indiretamente para 50% das mortes por doença cardiovascular (DCV) (MALACHIAS et al, 2016). A HAS tem sido apontada por diversos estudos tanto como o principal fator de risco para mortalidade quanto preditor de anos de vida saudáveis perdidos (DALY) (LIM et al, 2012;NASCIMENTO et al, 2012;CHOR et al, 2015). Define-se por hipertensão arterial sistêmica (HAS) como a elevação dos níveis pressóricos no valor acima de 140 mmHg para a pressão sistólica e 90 mmHg para a pressão diastólica (MALACHIAS et al, 2016;WILLIAMS et al, 2018).…”
Section: Introductionunclassified
See 1 more Smart Citation
“… 1 In spite of recent advances in clinical and interventional treatment, 2 , 3 ischemic heart disease (IHD) was responsible for 116,333 deaths in 2016, of which 80% were due to acute manifestations, principally in the form of acute myocardial infarction (AMI). 4 …”
mentioning
confidence: 99%
“…the hospital, has yet to be established in the literature. 4 It is also important to highlight that a recent study indicated that there are sex-specific differences, with greater delays being observed in women, mainly owing to atypical symptoms which lead to delays in the decision to seek healthcare. 5…”
mentioning
confidence: 99%